(untitled) - Carey, Steven D (New York, 1997)
This study guide accompanies "The physical universe", eight edition, by Krauskopt and Beiser. Each of the study guide's chapters is keyed to its counterpart in the text and contains a chapter summary, a sentence outline of the chapter, and additional review questions
Keywords: space sciences